(untitled) - Bui, Thi Phuong Nam (Netherlands, 2016)
The human intestinal tract harbours a trillion on microbial cells, predominantly anaerobes. The activity and physiology of these anaerobes is strongly associated with health and disease. This association has been investigated for a long time.However, this has not been fully understood. One of the reasons is the limited availability of cultured representatives. It is estimated that there may be more than 3000 species colonised in the gut of healthy individuals, however, only a bit over 1000 species have been isolated and characterised. Among the intestinal microbes, butyrate-producing bacteria are of special interest as the butyrate produced, is crucial to maintain a healthy gut. In addition, butyrate-producing bacteria have shown a reverse correlation with several intestinal diseases.
Keywords: Vi sinh vật,Microbiology